Iodine-induced thyroid dysfunction: a scientometric study and visualization analysis - Gong, Boshen; Wang, Xichang; Wang, Chuyuan; Yang, Wanyu; Shan, Zhongyan; Lai, Yaxin (Frontiers in Endocrinology, 2023)
Objective Iodine is essential in thyroid hormone production. Iodine deficiency is associated with serious complications (i.e miscarriage and stillbirth), whereas excess can cause thyroid dysfunction (i.e hyperthyroidism, hypothyroidism, thyroid autoimmunity). We conducted this scientometric study to visualize hot spots and trends in iodine-induced thyroid dysfunction over past two decades. The aim of this paper was to help scholars quickly understand the development and potential trend in this field, and guide future research directions. Methods Articles on iodine-induced thyroid dysfunction from 2000 to 2022 were retrieved from the Web of Science Core Collection (WoSCC) using the following search terms: (((((TS=(hypothyroid*)) OR TS=(hyperthyroid*)) OR TS= (“TSH deficiency”)) OR TS= (“thyroid stimulating hormone deficiency”)) AND TS=(Iodine)) NOT TS=(radioiodine). Only publications in English were selected. CiteSpace, VOSviewer, Tableau, Carrot2, and R software were used to analyze the contribution and co-occurrence relationships of different countries, institutes, keywords, references, and journals. Results A total of 2986 publications from 115 countries and 3412 research institutions were included. From 2000 to 2022, research on iodine-induced thyroid dysfunction progressed over a three-stage development period: initial development (2000-2009), stable development (2010-2016), and rapid development (2016-2022) period. The Journal of Clinical Endocrinology and Metabolism had the most co-citations followed and China Medical University (n=76) had the most publications. The top three clusters of co-citation references were isolated maternal hypothyroxinemia, subclinical hyperthyroidism, and brain development. Various scientific methods were applied to reveal acknowledge structure, development trend and research hotspots in iodine-induced thyroid dysfunction. Conclusion Our scientometric analysis shows that investigations related to pregnant women, epidemiology surveys, and iodine deficiency are promising topics for future iodine-induced thyroid dysfunction research and highlights the important role of iodine on thyroid function.